Cardiovascular Clinical Trials in a Pandemic: Immediate Implications of Coronavirus Disease 2019 - Ernest Spitzer; Ben Ren; Jasper J Brugts; Joost Daemen; Eugene McFadden; Jan GP Tijssen; Nicolas M Van Mieghem (Cardiac Failure Review)
The coronavirus disease 2019 (COVID-19) pandemic started in Wuhan, Hubei Province, China, in December 2019, and by 24 April 2020, it had affected >2.73 million people in 185 countries and caused >192,000 deaths. Despite diverse societal measures to reduce transmission of the severe acute respiratory syndrome coronavirus 2, such as implementing social distancing, quarantine, curfews and total lockdowns, its control remains challenging. Healthcare practitioners are at the frontline of defence against the virus, with increasing institutional and governmental supports. Nevertheless, new or ongoing clinical trials, not related to the disease itself, remain important for the development of new therapies, and require interactions among patients, clinicians and research personnel, which is challenging, given isolation measures. In this article, the authors summarise the acute effects and consequences of the COVID-19 pandemic on current cardiovascular trials.